Discovery of a Novel Molecule that Regulates Tumor Growth and Metastasis - Chery A. Whipple; Arthur D. Lander; Murray Korc (The Scientific World Journal)
The heparan sulfate proteoglycan, Glypican-1 (GPC1), significantly impacts the growth of pancreatic cancer cells in vivo and markedly attenuates tumor angiogenesis and metastasis in athymic mice. Interestingly, both cancer cell–derived and host-derived GPC1 play an important role in tumor development and spread. These data suggest that GPC1 may be a valid therapeutic target for pancreatic cancer.